Evaluation of Prosthodontic Function by Pronunciation of Test Sentences: the Present Situation, Problems Encountered, and Future Prospects - Yamagata, Kensuke (Nihon Hotetsu Shika Gakkai Zasshi, 2001)
Studies undertaken to establish a method for evaluating speech disorders from the standpoint of orofacial articulatory movements of edentulous and cleft palate subjects during the pronunciation of Japanese test sentences, are reviewed. To form certain speech sounds, the tongue touches various portions of the teeth, the alveolar ridge, and the palate. When these structures are replaced or covered by a prosthetic appliance, proprioceptive feedback may be altered, so that speech articulation is disturbed. In this regard, static palatography and dynamic palatography were used to identify the contact patterns of tongue-to-palate and tongue-to-teeth movements. These methods were applied to determine the degree of misarticulation of cleft palate patients undergoing prosthetic therapy. To determine the vertical dimension of occlusion (O. V. D.) by phonetic, methods in which the trajec-tories of face markers and the voice can be simultaneously recorded were designed, and the mandibular positions during speech were observed. The time frame during which each consonant was pronounced was identified based on a sound spectrogram. In cases of maxillofacial deformity, the mandibular positions during pronunciation of the test sentences were observed at various O. V. D. s, to predict acceptable occlusion. Further, to assess the speech pattern of edentulous patients, three-dimensional orofacial movements during speech were also observed. In these studies, real-time speech spectrum analysis was useful to relate orofacial articulatorymovements and time-points for production of consonants in the test sentences.